Proximal femoral density distribution and structure in relation to age and hip fracture risk in women. (15th February 2013) - Carballido‐Gamio, Julio; Harnish, Roy; Saeed, Isra; Streeper, Timothy; Sigurdsson, Sigurdur; Amin, Shreyasee; Atkinson, Elizabeth J; Therneau, Terry M; Siggeirsdottir, Kristin; Cheng, Xiaoguang; Melton, L Joseph; Keyak, Joyce; et al.
Abstract Hip fracture risk rises exponentially with age, but there is little knowledge about how fracture‐related alterations in hip structure differ from those of aging. We employed computed tomography (CT) imaging to visualize the three‐dimensional (3D) spatial distribution of bone mineral density (BMD) in the hip in relation to age and incident hip fracture. We used intersubject image registration to integrate 3D hip CT images into a statistical atlas comprising women aged 21 to 97 years (n = 349) and a group of women with (n = 74) and without (n = 148) incident hip fracture 4 to 7 years after their imaging session. Voxel‐based morphometry was used to generate Student's t test statistical maps from the atlas, which indicated regions that were significantly associated with age or with incident hip fracture. Scaling factors derived from intersubject image registration were employed as measures of bone size. BMD comparisons of young, middle‐aged, and older American women showed preservation of load‐bearing cortical and trabecular structures with aging, whereas extensive bone loss was observed in other trabecular and cortical regions. In contrast, comparisons of older Icelandic fracture women with age‐matched controls showed that hip fracture was associated with a global cortical bone deficit, including both the superior cortical margin and the load‐bearing inferior cortex. Bone size comparisons showed larger dimensions in older compared to younger American women and in older Icelandic fracture women compared to controls. The results indicate that older Icelandic women who sustain incident hip fracture have a structural phenotype that cannot be described as an accelerated pattern of normal age‐related loss. The fracture‐related cortical deficit noted in this study may provide a biomarker of increased hip fracture risk that may be translatable to dual‐energy X‐ray absorptiometry (DXA) and other clinical images. © 2013 American Society for Bone and Mineral Research.